The Saga of Dakota Territory's First Railroad - Garry, Patrick M. author. aut Link
XIII, 173 p. 10 illus.
Keywords: "Professor Garry brilliantly tells a tale of grit and self-determination by pioneers in Dakota Territory and re-imagines what we now think Western history to be. Garry's work is exceptional, unique, and surprising. It is a soothing cool breeze in desiccated and barren academic landscape." —Jon K. Lauck, Editor-in-Chief, Middle West Review This book focuses on a key case study in the history of American territories, public works, transportation and the constitutional system of checks and balances. The saga of Yankton County’s attempt to bring the first railroad into Dakota Territory in 1873 covers 25 years of territorial history, leading up to statehood for South Dakota in 1889. Garry investigates the array of unusual facts and occurrences within the story of the Dakota Southern, which was the first railroad stretching into the Territory. Lawsuits worked themselves all the way up to the Supreme Court. The most notorious shooting in the territory occurred in connection with railroad disputes The failure of Yankton to pay interest on the bonds used to finance the railroad—a failure initially prompted by a court injunction against such payment—may have delayed statehood for the entire territory. But the primary focus of this railroad story revolves around the way it highlights the predictions and observations of two of America’s most noted thinkers: Alexis de Tocqueville and James Madison. It shows the tension between Tocqueville’s impressions of the enterprising, risk-taking, and association-minded nature of Americans and Madison’s warnings about a federal government exercising unprecedented powers and having expanded beyond adequate checks. It works through the abstract observations of Tocqueville and Madison with tangible examples that are still relevant today. Patrick M. Garry is Professor of Law at the University of South Dakota School of Law, USA. He has published widely on US constitutional history.